Um procedimento para investigar aprendizagem discriminativa e formação de classes funcionais em cães (Canis familiaris) - Montagnoli, Tathianna Amorim Souza (2012)
The investigation of symbolic or pre-symbolic behavior in dogs requires the establishment of arbitrary relations among stimuli. A way to teach such relations is requiring a common response in the presence of each one of them, which can result in a class of functionally equivalent stimuli. This study aimed to investigate the formation of functional classes with four dogs. For this purpose it was used an automated device for emission and recording of operant responses and for the presentation of visual stimuli. The operant response was to nose poke a stimuli which were presented in a touch-screen monitor. Three sets of two stimuli (A1/A2; B1/B2; C1/C2) were used for three dogs and two sets of two stimuli (C1/C2; E1/E2) were used for the other dog. In each set, one stimulus was related to reinforcement (S+) and the other to extinction (S-), regarding tasks of simultaneous simple discrimination. Five experimental phases were programmed for three dogs: I) Training and reversals of pair A stimuli; II) Training and reversals of pair B; III) Training and reversions of AB being presented in the same session with functional class formation probes; IV) Training and reversals of pair C; and V) Training and reversals of ABC with functional class formation probes. On the third and fifth phases stimuli of the same set (A1 and B1 or A1, B1 and C1, respectively) were established as S+, and the stimuli of the other set (A2 and B2 or A2, B2 and C2) as S-. After baseline was acquired and reached stability the functions of the stimuli were reversed repeatedly (S+ began to function as S- and vice versa), and it was appraised if the animals reverted the functions of the other stimuli given the reversal of the first pair in one of the sets, and that before direct exposure to new contingencies which would indicate functional classes formation (S+ class and S- class). For the fourth dog four experimental phases were programmed: I) Training of pair E stimuli (without reversal); II) Training of pair C stimuli; III) Training of CE being presented in the same session; and IV) Three reversions of CE being presented in the same session. The results show that the procedure was able to establish a complex and flexible discriminative repertoire in dogs, but insufficient to demonstrate relational responding in the only animal to be exposed to the functional class probes. Nevertheless, considerations were made about the positive aspects of the proposed procedure and learning set formation.